64 Preventing adolescent violence using the communities that care prevention system: findings from a community-randomised trial. (9th June 2015) - Oesterle, Sabrina; Hawkins, David J; Kuklinski, Margaret R.; Fleming, Christopher; Rhew, Isaac C.; Brown, Eric C.; Abbott, Robert D.; Catalano, Richard F.
Abstract : Statement of purpose: Texting while driving (TWD) is a critical problem for teen drivers, increasing risk for crashes. The purpose of this analysis was to describe how teen drivers' control their TWD. Methods: We collected quantitative and qualitative data from 30 teens, ages 16–18, licensed for ≤1 year in Pennsylvania. Frequencies from quantitative self-report data were used to describe teens' views and descriptive content analysis from focus group interviews was used to develop themes related to TWD. Results: Teens had a mean age 17.39 (sd 0.52), mean length of licensure 173.7 days (sd 109.2) and were 50% male and predominately white (90%) and non-Hispanic (97%). Over 53% of the sample reported 0 days of TWD in the past month; 96.7% thought it was a bad/very bad idea; and of people important to them, 100% would disapprove of TWD. Focus group data indicated that not all teens defined TWD systematically; some teens did not consider reading a text as TWD. TWD was also context dependent. The nature of the relationship to the other person engaged in texting, purpose of conversation, weather and traffic patterns all contributed to texting decisions. Teens avoided TWD by turning off phones and using passengers; opportunities at stop lights were a "safer" way to text. Conclusions: Teens view texting and driving as unsafe and describe Methods in which they control TWD behaviours. However, some Methods still take attention off the focus of driving. Significance and contribution to the field: TWD is a contributor to motor vehicle crashes in teens and effective interventions to decrease risks are needed. Teens could benefit from strategies that stress the importance of focused attention on the roadway at all times during the driving trip and provide teens with the tools to avoid responding to texts that they receive while driving.